INTEGRASI PASAR SPASIAL TELUR AYAM RAS DI PROVINSI BENGKULU - Silalahi, Romauliyana Br.; Romdhon, M. Mustopa; Badrudin, Redy (Jurnal AGRISEP, 2017)
This research is the integration of the market of “Telur Ayam Ras”  in the Bengkulu Province. The analized district that are the City of Bengkulu, South Bengkulu District, North Bengkulu District, and Rejang Lebong District. The purpose of this research was to analyze the price developments and analyze spatial market integration of “telur ayam ras”. The data used is secondary data which is data price of “Telur Ayam Ras” in Bengkulu Province per month and taken during the past 10 years, starting in 2004 untill 2013. The analyze was performed by descriptive for price developments and to analyze spatial market integration is using Eviews 6 applications. Results of the research showed that the price development in the four districts fluctuates due to the influence of demand and supply, while integration of spatial market of eggs in the Bengkulu Province has already well integrated and there are two pairs of districts that interplay in the formation of prices, those are Bengkulu City with Rejang Lebong and South Bengkulu with North Bengkulu.